AKTIVITAS ANTIMIKROBA KOMBINASI REBUSAN DAUN SIRIH HIJAU (Piper betle) DAN DAUN SIRIH MERAH (Piper crocatum) TERHADAP Candida albicans. - Diani Kurniawati; MG. Isworo Rukmi; Arina Tri Lunggani (Jurnal Akademika Biologi, 2014)
Piper betle and Piper crocatum leaf extract each has proven to have antimicrobe effect against Candida albicans, this is the reason why piper betle leaf often used as mixture of mouthwash or vagina cleanser. This research aim is to know the antimicbial activity of combination between stewed piper betle and piper crocatum leaf against Candida albicans. Experimental design that used is Completely Randomized Design (CRD) factorial design with 2 factor. Combination  of stewed green betel leaf and red betel leaf respectively 100% P.betle and 0% P. crocatum; 75% P.betle and 0% P. crocatum; 50% P.betle and 50% P. crocatum; 25%  P.betle and 75% P. crocatum; 0% P.betle and 100% P. crocatum. A negative control is steril aquadest, while second factor is contact time 0, 30 and 60 minute. The variables meansured were the growth of colonies in each treatment combination. The result showed that combination of 100% P.betle and 0% P. crocatum; 75% P.betle and 0% P. crocatum; 50% P.betle and 50% P. crocatum; 25%  P.betle and 75% P. crocatum have antimicrobial activity is  high. This result proven by absence of colony growth after treatment. The best antimicrobial activity found on treatment with only addition of red betel at 60 minutes of contact time. Keywords : Piper betle, Piper crocatum, antimicrobial, Candida albicans